Fenomena overload aktivitas mahasiswa muslim: analisis manajemen waktu antara kuliah, kerja paruh waktu, dan ibadah - mafazah, nida nailil (Maliki Interdisciplinary Journal, 2026)
This article examines the phenomenon of activity overload among Muslim students who attend university while working part-time and maintaining religious obligations. The study aims to analyze the forms of overload, the patterns of time management between study, work, and worship, and the supporting and inhibiting factors that influence these patterns. A quantitative literature review approach is employed by synthesizing journal articles on part-time work, time management, academic stress, and spirituality among Muslim students published over the last ten years. The review shows that part-time work without adequate time and self-management increases the risk of academic stress, lower achievement, and reduced worship quality, whereas the combination of effective time management, academic hardiness, and strong spirituality helps students maintain a healthier balance between study, work, and worship roles. These findings highlight the need to strengthen time-management skills and provide institution-based support grounded in Islamic values for Muslim students who engage in part-time employment.